Assessing the Effects of Treated Wastewater Irrigation on Soil Physico-Chemical Properties - Sdiri, Wiem; AlSalem, Huda S.; Al-Goul, Soha T.; Binkadem, Mona S.; Ben Mansour, Hedi (Sustainability, 2023)
For assessing the effects of wastewater on soil physical and chemical properties, manual irrigation (MI) and surface drip irrigation (SDI) systems were investigated. The experiment was conducted over 12 months. Before and after the experiment, soil samples were collected from three depths (0–20 cm, 20–40 cm and 40–60 cm) for analysis. The obtained results indicated that wastewater application probably preserves soil quality by maintaining its pH-water values whatever the irrigation system used. This study suggested that nutrient input from wastewater promotes soil microbial activity and organic matter (OM) mineralization. In fact, at the soil depths of 0–20 cm and 20–40 cm, MI using treated wastewater (TWW) leads to decrease OM content. P input may justify treated wastewater fertilizing effect in the topsoil. Moreover, TWW fertilizing effect was demonstrated by increased potassium (K) amount in the two upper soil layers (0–20 cm and 20–40 cm) following SDI system. This last system may block metals (iron (Fe), copper (Cu), cobalt (Co) and selenium (Se)) translocation to plants and their accumulation in soil. In contrast, metal translocation was maintained by the MI system. The present data is encouraging to reuse TWW for agricultural purposes, especially for orchard irrigation.